The Intertextuality of Qur’anic Verses in Shaping Moral Discourse in Nasa’ih al-‘Ibad by Shaykh Nawawi al-Bantani - Arwansyah bin Kirin; Alven Putra; Edriagus Saputra; Muhammad Rezi (Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2026)
-